CONCEPT OF CAREER GUIDANCE AND COUNSELING FOR JUNIOR HIGH SCHOOL STUDENTS - Anjani, Aprilia; Rahdefa Putri, Azzahra; Muthia Afifah, Fiska (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
This journal discusses the concept of career counseling which is useful for determining career choices by students. Career is an important thing in an individual's life. Careers will continue to be continued and developed by individuals throughout their lives. From an early age, he was introduced to various kinds of jobs that he would enter when he grew up. The purpose of writing this literature study is to find out the influence and application of morning career counseling on junior high school teenagers' career choices. The method used is a systematic review through analysis of articles about the use of career counseling for junior high school teenagers. The research object is a collection of several articles from various sources. This article was searched in Indonesian using access from internet searches and also from databases, namely: Google search engine, Google Scholar and Google Books with the keywords Middle School Teenage Career. The method used is a systematic review through analysis of articles about the use of career counseling for junior high school teenagers. The research object is a collection of several articles from various sources. This article was searched in Indonesian using access from internet searches and also from databases, namely: Google search engine, Google Scholar and Google Books with the keywords Middle School Teenage Career